2021
DOI: 10.1042/ns20210021
|View full text |Cite
|
Sign up to set email alerts
|

α-synuclein pathogenesis in hiPSC models of Parkinson’s disease

Abstract: α-synuclein is an increasingly prominent player in the pathology of a variety of neurodegenerative conditions. Parkinson’s disease (PD) is a neurodegenerative disorder that affects mainly the dopaminergic neurons in the substantia nigra of the brain. Typical of PD pathology is the finding of protein aggregations termed ‘Lewy bodies’ in the brain regions affected. α-synuclein is implicated in many disease states including dementia with Lewy bodies and Alzheimer’s disease. However, PD is the most common synuclei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…The efficiency of DA neuron induction in vitro with these modified protocols has been shown to be similar across different cell lines of different genetic backgrounds including those carrying mutations in genes associated with PD such as the SNCA triplication (α-synuclein triplication) cell liner. When iPSCderived DA neurons from PD-affected individuals are probed further, independent of genetic cause, they have been shown to display cardinal features of neurodegeneration including formation of α-synuclein aggregates, dysregulation of neurotransmission, and increased susceptibility of DA neurons, relative to non-DA neurons, to diverse neurotoxins as indicated by cell death and overexpression of markers of oxidative stress, culminating in cell death (Byers et al, 2011;Nguyen et al, 2011;Baena-Montes et al, 2021;Diao et al, 2021;Fukusumi et al, 2021;Lin et al, 2021;Drouin-Ouellet et al, 2022). Whether the PD features observed correspond to changes in vivo in the midbrain was also addressed, at least in part, in studies that compared transcriptional profiles of human induced and primary midbrain dopaminergic neurons (Xia et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of DA neuron induction in vitro with these modified protocols has been shown to be similar across different cell lines of different genetic backgrounds including those carrying mutations in genes associated with PD such as the SNCA triplication (α-synuclein triplication) cell liner. When iPSCderived DA neurons from PD-affected individuals are probed further, independent of genetic cause, they have been shown to display cardinal features of neurodegeneration including formation of α-synuclein aggregates, dysregulation of neurotransmission, and increased susceptibility of DA neurons, relative to non-DA neurons, to diverse neurotoxins as indicated by cell death and overexpression of markers of oxidative stress, culminating in cell death (Byers et al, 2011;Nguyen et al, 2011;Baena-Montes et al, 2021;Diao et al, 2021;Fukusumi et al, 2021;Lin et al, 2021;Drouin-Ouellet et al, 2022). Whether the PD features observed correspond to changes in vivo in the midbrain was also addressed, at least in part, in studies that compared transcriptional profiles of human induced and primary midbrain dopaminergic neurons (Xia et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the aggregation of abnormal proteins in the brain is one of the mechanisms that induce the neurotoxicity observed in neurodegenerative diseases ( Daniele et al, 2018 ), such as the neurofibrillary tangle caused by hyperphosphorylated tau aggregation in AD brains ( Masters et al, 1985 ; Perry et al, 1987 ), the formation of Lewy bodies in PD brains ( Litvan et al, 1998 ), or Skein-like inclusions or Busina bodies in ALS ( Leigh et al, 1991 ; Okamoto et al, 2008 ). Previous research showed evidence that partially replicated the early-stage disease’s pathophysiology by utilization of iPSCs derived neuronal cells in vitro ( Sances et al, 2016 ; Cobb et al, 2018 ; Chang et al, 2020 ; Klimmt et al, 2020 ; Baena-Montes et al, 2021 ; Fares et al, 2021a , b ; Giacomelli et al, 2022 ). If late-stage pathophysiology with such findings can be reproduced in culture dishes, the scope of research may be expanded to find ways to reduce or reverse neurodegenerative pathology by manipulating new therapeutic pathways ( Figure 1 ).…”
Section: Strategies For Manipulating the Cell Age Of Induced Pluripot...mentioning
confidence: 99%
“…Tissue accumulation of defective α-synuclein is one of the key features of PD. Being present intracellularly or in the extracellular space, this protein produces prominent neurotoxic effects, alters synaptic plasticity, affects autophagy, induces mitochondrial dysfunction and endoplasmic reticulum stress, deregulates intercellular communication, and supports the development of neuroinflammation, thereby providing propagation of pathological events leading to the establishment of a PD-specific phenotype [21,26,28,29]. Moreover, there is a documented transneuronal propagation of abnormal α-synuclein aggregates in PD, leading to prion-like synuclein dissemination within the nervous tissue [30,31].…”
Section: Aberrant Neurogenesis In Parkinson S Diseasementioning
confidence: 99%
“…In addition, severe changes in neuronal differentiation and maturation have been detected upon SNCA triplication, whereas the knock-down of SNCA mRNA in iPSC-derived cells prevents such abnormalities [82]. A53T point mutation in the SNCA gene in iPSC-derived neurons results in the development of pathological alterations in cell metabolism and defective proteostasis, early neurite degeneration, and down-regulation of some synaptic proteins [28]. Interneuronal spreading of α-synuclein within and between iPSCs cortical neurons was reproduced in the in vitro microfluidic systems allowing unidirectional axonal growth [83].…”
Section: Generation Of Ipsc-derived Dopaminergic Neuronsmentioning
confidence: 99%